Social Policies for a Recovery - Herwig Immervoll; Ana Llena-Nozal (Institute for the Study of Labor (IZA), 2011)
The fallout from the global economic downturn of 2008-09 is a continuing source of stress on families and a constraint on government policies. How can social policies contribute to a quick and equitable recovery from the crisis and how can they best respond to the difficulties that households continue to face? What role can and should social policy budgets play in improving the budget outlook of countries facing unsustainable government debt? And how should governments prioritise different areas of social spending when faced with heightened demand for support but, often, much reduced fiscal space? This paper addresses these questions in light of countries' experiences during the most recent and earlier economic downturns.
Keywords: I38; J08; H20; H60; 330; economic crisis; social policy; redistribution; unemployment; government spending; Sozialpolitik; Öffentliche Sozialleistungen; Wirtschaftskrise; Öffentliche Schulden; Arbeitslosigkeit; Verteilungswirkung; OECD-Staaten